2014
DOI: 10.1002/cssc.201402313
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Analysis within Pharmaceutical Process Optimization and Intensification: Case Study of Active Pharmaceutical Ingredient Production

Abstract: As the demand for new drugs is rising, the pharmaceutical industry faces the quest of shortening development time, and thus, reducing the time to market. Environmental aspects typically still play a minor role within the early phase of process development. Nevertheless, it is highly promising to rethink, redesign, and optimize process strategies as early as possible in active pharmaceutical ingredient (API) process development, rather than later at the stage of already established processes. The study presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 48 publications
2
76
0
1
Order By: Relevance
“…Finally, one aggregated environmental efficiency value can be calculated by means of weighting factors. 72,73 Furthermore, the results are transferable to, e.g., a bi-objective eco-portfolio depiction showing environmental and cost efficiency in one graph. Thereby, cost efficiency is typically calculated taking into account relevant variable and fixed production cost criteria, e.g., investment, material, energy, personnel, and waste treatment costs.…”
Section: Coupling With Other Assessment Methodsmentioning
confidence: 99%
“…Finally, one aggregated environmental efficiency value can be calculated by means of weighting factors. 72,73 Furthermore, the results are transferable to, e.g., a bi-objective eco-portfolio depiction showing environmental and cost efficiency in one graph. Thereby, cost efficiency is typically calculated taking into account relevant variable and fixed production cost criteria, e.g., investment, material, energy, personnel, and waste treatment costs.…”
Section: Coupling With Other Assessment Methodsmentioning
confidence: 99%
“…An LCA study provides a detailed analysis of possible environmental impacts of products and processes during the life of the product . Pharmaceutical researchers have studied and consistently use LCA technology in efforts to reduce environmental footprints through process optimization . Other researchers have used LCAs to quantify the environmental impacts of medical equipment (eg, computerized tomography scanners, steam sterilizers), obstetrical and gynecological procedures (eg, hysterectomies), and textiles (eg, isolation gowns) …”
Section: Literature Reviewmentioning
confidence: 99%
“…The results revealed that transport intensification in the micro-reactor had the potential to be favourable, by accelerating the reaction, but longer reaction times and higher temperatures would be needed to have sufficient yields and oxirane numbers. [59] The simulation of the chemical intensification in a Plug Flow Reactor (PFR) ; [54] reproduced with permission from WILEY-VCH). AP, acidification potential.…”
Section: Mythen's Soybean Oil Epoxidation At Fine-chemical Scale-eu'smentioning
confidence: 99%